Practical biochemistry - Damodaran K., Geetha (New Delhi, India : Jaypee, 2016)
The motive behind writing practical biochemistry was to make the practical concepts of biochemistry clar for medical students in an examination-oriented format. In this edition, most of the diagrammatic figures are replaced by real images in qualitative analysis and spotters sections. This will definitely impart a realistic feeling of learning qualitative test.
Contents 1. Reactions of carbohydrates 2. Reactions of proteins 3. Reactions of lipids 4. Reactionsof urea 5. Reactions of creatinine y otros veinte màs....
Incluye Index
Contiene Contents
Keywords: ANALISIS -- QUÍMICOS; BIOQUIMICA; REAACCIONES